IMF Survey, Volume 37, Issue 07. (IMF Survey; IMF Survey ;, 2008)
Inflation, IMF work agenda, Food and fuel prices, Commodity price surge, Oil price surge, Jeddah meeting, Haiti interview, Norway's sovereign wealth fund, Mexico, Switzerland's monetary policy, Mauritius, News briefs.